Emerging Biomaterials‐Based Strategies for Inhibiting Vasculature Function in Cancer Therapy. Issue 7 (16th June 2021) - Liu, Minting; Wu, Caisheng; Ke, Lingjie; Li, Zhiguo; Wu, Yun‐Long
Abstract: The constant feeding of oxygen and nutrients through the blood vasculature has a vital role in maintaining tumor growth. Interestingly, recent endeavors have shown that nanotherapeutics with the strategy to block tumor blood vessels feeding nutrients and oxygen for starvation therapy can be helpful in cancer treatment. However, this field has not been detailed. Hence, this review will present an exhaustive summary of the existing biomaterial based strategies to disrupt tumor vascular function for effective cancer treatment, including hydrogel or nanogel‐mediated local arterial embolism, thrombosis activator loaded nano‐material‐mediated vascular occlusion and anti‐vascular drugs that block tumor vascular function, which may be beneficial to the design of anti‐cancer nanomedicine by targeting the tumor vascular system. Abstract : This review focuses on biomaterials as therapeutic tools against the inhibition of tumor vascular function. In terms of therapeutic strategies, the transarterial embolic potential of hydrogel polymers, nanodrug delivery systems loaded with anti‐vascular drugs, or with coagulation‐active molecules will be described in detail.